Hopeful Losers? A Moral Case for Mixed Electoral Systems - King, Loren (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2015)
Liberal democracies encourage citizen participation and protect our freedoms, yet these regimes elect politicians and decide important issues with electoral and legislative systems that are less inclusive than other arrangements. Some citizens inevitably have more influence than others. Is this a problem? Yes, because similarly just but more inclusive systems are possible. Political theorists and philosophers should be arguing for particular institutional forms, with particular geographies, consistent with justice.